2023
DOI: 10.3390/membranes13040448
|View full text |Cite
|
Sign up to set email alerts
|

Performance of TiO2-Based Tubular Membranes in the Photocatalytic Degradation of Organic Compounds

Abstract: This work presents the photocatalytic degradation of organic pollutants in water with TiO2 and TiO2/Ag membranes prepared by immobilising photocatalysts on ceramic porous tubular supports. The permeation capacity of TiO2 and TiO2/Ag membranes was checked before the photocatalytic application, showing high water fluxes (≈758 and 690 L m−2 h−1 bar−1, respectively) and <2% rejection against the model pollutants sodium dodecylbenzene sulfonate (DBS) and dichloroacetic acid (DCA). When the membranes were submerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…This makes photocatalytic membranes promising candidates for sustainable and efficient water treatment processes. Several studies have demonstrated the effectiveness of photocatalytic membranes in various water treatment applications [11][12][13][14][15][16]. Moreover, the integration of photocatalytic materials into membrane structures can enhance the selectivity and specificity of membranes for particular contaminants, making them suitable for targeted water treatment applications.…”
Section: Introductionmentioning
confidence: 99%
“…This makes photocatalytic membranes promising candidates for sustainable and efficient water treatment processes. Several studies have demonstrated the effectiveness of photocatalytic membranes in various water treatment applications [11][12][13][14][15][16]. Moreover, the integration of photocatalytic materials into membrane structures can enhance the selectivity and specificity of membranes for particular contaminants, making them suitable for targeted water treatment applications.…”
Section: Introductionmentioning
confidence: 99%